Simulation of Glacial Lake Outburst Flood in Southeastern Qinghai-Tibet Plateau—A Case Study of JiwenCo Glacial Lake - Zhang, Yuan; Yao, Xiaojun; Duan, Hongyu; Wang, Qi (Frontiers in Earth Science, 2022)
Glacial lake outburst floods (GLOFs) is one of the main natural disasters in alpine areas, which can cause extreme destruction to downstream settlements and infrastructures. A moraine-dammed lake named JiwenCo glacial lake (JGL) in the southeastern Qinghai-Tibetan Plateau failed on 26 June 2020, destroying many buildings, roads, bridges and farmlands along the flow path. We reconstructed the process of this GLOF event by the Hydrological Engineering Center’s River Analysis System (HEC-RAS) and examined the JGL’s evolution (area, length and volume) before its outburst, based on the measured cross-sections and hydrological data, videos and pictures taken by inhabitants, DEM data and Landsat Thematic Mapper (TM)/ Enhanced Thematic Mapper (ETM+)/ Operational Land Imager (OLI) images. The result showed that area, length and volume of the JGL increased by 0.20±0.07 km2, 0.66±0.03 km and 0.03±0.001 km3 from 1988 to 2020 (before the outburst), respectively. Approximately 0.05 km3 of water volume was discharged with the dropped water-level of 15.63 m after the outburst. The peak flow was 534.4 m3/s at breach and increased to 1408.11 m3/s at Zhongyu town. The difference between simulated and measured peak flow in Zhongyu town was 41.88 m3/s (3.53%), showing the high accuracy of the modelling results. For villages along the river-channel, the highest velocity was found in Yiga village (14.23 m/s) and the lowest was in Gongwa village (1.22 m/s). The maximum depth was gradually increased as the river reached downstream, 8.03 m in Yiga village and 50.96 m in Duiba village. The combination of landslide, high temperature and extremely heavy precipitation resulted in this GLOF disaster. An integrated disaster prevention and mitigation plan needs to be developed for susceptible areas like Niduzangbo basin that experienced two GLOFs in recent ten years.